Ed. F. Kruse of Blue Bell Creameries - MacInerney, Dorothy McLeod (Texas A & M University Press, 2016)
This biography of ice cream entrepreneur Ed. F. Kruse (1928-2015) looks back on a life devoted to family, community, and building one of the most successful businesses in Texas. Starting at Blue Bell Creameries at the age of thirteen, Kruse held every position imaginable at the company, eventually becoming president and chief executive officer. Under his guidance, Blue Bell grew from a creamery serving the small communities around Brenham, Texas, to a nationally recognized brand. Dorothy MacInerney takes readers behind the scenes at the "little creamery in Brenham." She reveals the hard work,